Analisis Kepatuhan Syariah E-Wallet Dana Berdasarkan Fatwa DSN-MUI No. 116/2017 - Yayuk Nailis Syarifatus Sa’diyah; Andriani Samsuri (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2026)
The rapid growth of e-wallet services in Indonesia has increased the need to evaluate their compliance with Islamic financial principles, particularly because most users are Muslims. Although DSN-MUI Fatwa No. 116/DSN-MUI/IX/2017 provides the regulatory framework for sharia-compliant electronic money, its implementation by commercial e-wallet providers remains underexplored. This study employed a descriptive qualitative approach using document analysis of DANA's terms and conditions, Bank Indonesia and Financial Services Authority (OJK) regulations, and the fatwa. The findings indicate that DANA's operations incorporate three Islamic contracts (akad): wadi'ah yad dhamanah for balance custody, wakalah bil ujrah for payment services, and ijarah for platform services. However, compliance gaps remain regarding sharia-compliant float fund placement, the absence of a Sharia Supervisory Board, and partner services based on conventional financing. These findings suggest that DANA has a solid foundation for developing a fully sharia-compliant digital payment ecosystem through stronger governance and institutional compliance. This study contributes to the literature on Islamic financial technology and provides practical recommendations for advancing sharia-compliant digital payment services in Indonesia.